Dynamics of an MDOF rotor stator contact system - Alexander Shaw (IMAC XXXIV, 2016)
The vibrations of rotating machinery are an important issue in many engineered systems, from aircraft engines todrilling platforms. In many cases there is a possibility of rotor stator contact, which leads to non-smooth nonlinearities;this leads to complex multi period responses in a single rotor system, and poses a challenging problem whenmore degrees of freedom are considered. In this work we examine how interaction of the underlying modes of atwo disc rotor, can lead to complex multi-period responses with intermittent contact. These motions can be excitedat driving speeds that are well removed from the linear critical speeds of the rotor. However, it is demonstrated thatthe driving frequencies can be predicted and explained by synchronisation between two modal responses and thedriving frequency.